Diode-laser-assisted esthetic gingival depigmentation: A case series - Hyder, Tahira; Arshad, Danial; Zafar, Salman (Hasanuddin University, 2023)
Although a benign condition of no medical concern, patients in Pakistan commonly complain of â€œblack gumsâ€ especially those with high lip line and esthetic concerns. Dentists have been correcting this condition with a wide range of treatment modalities, including diamond bur gingivectomy, scalpel gingivectomy with or without subsequent free gingival autografting, electrosurgery, cryosurgery, laser surgery. In this case series, a diode laser was used for depigmentation, which yielded good esthetic results, patient satisfaction and no pain or infection.Â